Attenuation of prostaglandin E2 elimination across the mouse blood-brain barrier in lipopolysaccharide-induced inflammation and additive inhibitory effect of cefmetazole - Akanuma Shin-ichi; Uchida Yasuo; Ohtsuki Sumio; Tachikawa Masanori; Terasaki Tetsuya; Hosoya Ken-ichi (Fluids and Barriers of the CNS, 2011)
Abstract Background Peripheral administration of lipopolysaccharide (LPS) induces inflammation and increases cerebral prostaglandin E2 (PGE2) concentration. PGE2 is eliminated from brain across the blood-brain barrier (BBB) in mice, and this process is inhibited by intracerebral or intravenous pre-administration of anti-inflammatory drugs and antibiotics such as cefmetazole and cefazolin that inhibit multidrug resistance-associated protein 4 (Mrp4/Abcc4)-mediated PGE2 transport. The purpose of this study was to examine the effect of LPS-induced inflammation on PGE2 elimination from brain, and whether antibiotics further inhibit PGE2 elimination in LPS-treated mice. Methods [3H]PGE2 elimination across the BBB of intraperitoneally LPS-treated mice was assessed by the brain efflux index (BEI) method. Transporter protein amounts in brain capillaries were quantified by liquid chromatography-tandem mass spectrometry. Results The apparent elimination rate of [3H]PGE2 from brain was lower by 87%, in LPS-treated mice compared with saline-treated mice. The Mrp4 protein amount was unchanged in brain capillaries of LPS-treated mice compared with saline-treated mice, while the protein amounts of organic anion transporter 3 (Oat3/Slc22a8) and organic anion transporting polypeptide 1a4 (Oatp1a4/Slco1a4) were decreased by 26% and 39%, respectively. Either intracerebral or intravenous pre-administration of cefmetazole further inhibited PGE2 elimination in LPS-treated mice. However, intracerebral or intravenous pre-administration of cefazolin had little effect on PGE2 elimination in LPS-treated mice, or in LPS-untreated mice given Oat3 and Oatp1a4 inhibitors. These results indicate that peripheral administration of cefmetazole inhibits PGE2 elimination across the BBB in LPS-treated mice. Conclusion PGE2 elimination across the BBB is attenuated in an LPS-induced mouse model of inflammation. Peripheral administration of cefmetazole further inhibits PGE2 elimination in LPS-treated mice.